How to release capital requirements during a pandemic? Evidence from euro area banks - Cyril Couaillier; Alessio Reghezza; Costanza Rodriguez D'Acri; Alessandro Diego Scopelliti (European Central Bank (ECB), 2022)
This paper investigates the impact of the capital relief package adopted to support euro area banks at the outbreak of the COVID-19 pandemic. By leveraging confidential supervisory and credit register data, we uncover two main findings. First, capital relief measures support banks' capacity to supply credit to firms. Second, not all measures are equally successful. Banks adjust their credit supply only if the capital relief is permanent or implemented through established processes that foresee long release periods and affect their ability to distribute dividends. By contrast, discretionary relief measures are met with limited success, possibly owing to the un- certainty surrounding their capital replenishment path or because they did not affect dividend policy. Moreover, requirement releases were more effective for banks with a low capital head- room over requirements and did not trigger additional risk-taking. These findings provide key insights on how to design effective bank capital requirement releases in crisis time.
Keywords: E61; G01; G18; G21; 330; Bank capital requirements; Countercyclical policy; Macroprudential policy; Credit register; Coronavirus